Targeted steroid delivery for myelin oligodendrocyte glycoprotein antibody-associated rare optic neuritis: Clinical outcome and review literature - Shweta Singh; Sanjiv Kumar Gupta; Shaffi Chopra (Journal of Clinical Ophthalmology and Research)
Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is a rare inflammatory demyelinating disorder affecting the central nervous system and optic nerve, thus leading to optic neuritis as the most common manifestation. We report a case of a 29-year-old female who presented with sudden loss of vision in her right eye, followed by left eye, accompanied by headache, mild periorbital pain, hiccups, and nausea, without any weakness or relevant medical history. She was diagnosed with MOG antibody-associated demyelinating optic neuritis based on MRI and blood investigations. The patient was given intravenous methylprednisolone (IVMP) but showed no improvement. Subsequently, retrobulbar dexamethasone injection was administered, leading to significant and rapid vision recovery. This case suggests that retrobulbar dexamethasone injections can be an effective adjunct therapy for early and prompt recovery in patients with MOG antibody-associated optic neuritis when systemic treatments fail.